Hypopigmentation of transverse nasal line. - Cutrone, M. (European Journal of Pediatric Dermatology, 2007)
The patients presented, although due to different causes, a hypopigmentation level with the transverse nasal line. The latter is an embryonic junction line, along which erythema, discoloration, cyst, comedo, sometimes inherited by an autosomal dominant trait can be localized.